Measuring the volume of eroded material in ravines based on the use of photographs obtained with Remotely Piloted Aircraft (RPA) - Gomes, Luciano Nardini; Gomes, Eduardo Nardini [UNESP]; Alves Junior, Agostinho Prado (Univ Coimbra, Fac Letras, 2023)
Soil conservation is a fundamental process in agricultural systems, particularly when seeking a balance between productivity and the environment. When this is not taken into account, the soil is susceptible to the action of erosion processes, which can culminate in large areas eroded known as ravines, whose recovery always involves a significant financial cost and time. The measurement and digital cartographic representation of this type of phenomena have evolved a lot, when compared to traditional measurement methods. The use of Aircraft Remotely Piloted (ARP) is a technique with great development in the market for mapping and measuring the volume of eroded soil in ravines from the Digital Surface Model (MDS) based on aerial photogrammetry on images obtained by ARP, using conventional topography techniques as a control treatment. In a rural area with gullies measuring approximately 8.32 hectares, a topographic survey of 940 points was carried out using a laser total station and a GNSS L1/L2 receiver. 2 missions were carried out with low-cost RPA, with two perpendicular flight plans. The photos obtained were processed in the Agisoft Metashape software using different parameters in the generation of the point cloud. The volume of eroded material from the gully brought downstream was 638641.5 m(3), equivalent to 212,880 conventional buckets for transporting debris of 3 m(3).
Keywords: mapping; erosion volume; aerial photogrammetry; recovery of degraded areas; county of Anhembi